Boric acid-polyester long afterglow composite material as well as preparation method and application thereof
By developing rare earth-free boric acid-polyester long afterglow composite materials and simple heating preparation methods, combined with FRET strategy, a multi-color and adjustable color long afterglow effect is achieved, solving the problems of limited rare earth resources and single color, with high efficiency luminous performance and good application prospects.
Patent Information
- Application Number
- CN202510084405.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The use of rare earth elements in existing long afterglow polyester materials has problems of limited resources and high toxicity, and long afterglow materials with a single phosphorescence color are difficult to meet the demand for full-color phosphorescence or color-adjustable phosphorescence materials in real life.
A rare earth-free boric acid-polyester long afterglow composite material was developed. Through a simple heating preparation method, combined with the fluorescent resonance energy transfer (FRET) strategy, the molar ratio of fluorescent dyes and luminescents is adjusted to achieve multi-color, adjustable color long afterglow effect.
The high-efficiency luminescence performance and adjustment of afterglow color of rare earth-free long afterglow polyester has been achieved, and the high-pressure and complex process problems in the preparation of traditional materials have good application prospects and environmental friendliness.
Smart Images

Figure CN119775734A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of room temperature luminescent materials, and in particular relates to a boric acid-polyester long afterglow composite material and a preparation method thereof, and application of the long afterglow composite material. Background Art
[0002] Polyester is a common engineering material with simple processing and diverse functions. In recent years, it has occupied the largest commercial market share of polyester plastics with an annual global demand of over 80 million tons. Its market share among all plastic products is second only to polyethylene and polypropylene. It has been widely used in resins, films, electronic appliances and many other fields.
[0003] Long afterglow polyester materials are usually composed of rare earth-based luminophores and polyester, and are widely used in special clothing, anti-counterfeiting and safety instructions (see: Text. Res. J., 2012, 82 (7): 677-684; Shanghai Textile Science and Technology, 2013, 41 (4): 37-38; CN 115322529 A; CN 111455652 B; CN 112941660A). However, rare earth elements have the disadvantages of limited resources and high toxicity, which are harmful to human health, plants and soil ecosystems, hindering the further development of long afterglow polyester materials (see: Geoscience Frontiers, 2019, 10 (4): 1285-1303; CN 113735795 B). In these rare earth-doped long-afterglow polyester materials, polyester is usually used as a substrate rather than a luminescent body. However, polyester itself contains luminescent groups that can emit phosphorescence. However, since the phosphorescence emitted by polyester itself is too short, it cannot be put into practical application.
[0004] In addition, long afterglow materials with a single phosphorescent color are difficult to meet the demand for full-color phosphorescent or color-adjustable phosphorescent materials in real life. At present, wide color gamut adjustment of afterglow color is a problem that needs to be solved. Adopting certain strategies to make long afterglow materials have multi-color, adjustable emission characteristics and excellent processability will make long afterglow polyester materials have a wider application space. Fluorescence resonance energy transfer (FRET) strategy is an effective way to solve the above problems. FRET is a process in which energy is transferred from a donor to an acceptor, which will lead to a decrease in the luminescence intensity of the donor and an increase in the luminescence intensity of the acceptor. Due to the existence of the FRET phenomenon, the luminescent material has a larger Stokes shift, and the wavelength position of the excitation and emission can be adjusted to achieve the properties of absorbing the energy of the luminophore and emitting multi-color fluorescence and phosphorescence (see: CN 116218518A; CN 113637195B). Therefore, the development of the luminescent properties of polyester itself and the adjustment of afterglow color are very important for the large-scale production and utilization of long afterglow materials, as well as environmental protection and bio-friendliness, and have good development prospects. Summary of the invention
[0005] In view of the shortcomings of limited rare earth element resources and high toxicity, as well as the problem of wide color gamut adjustment of afterglow color, the present invention provides a color-adjustable rare earth-free long afterglow composite material - boric acid-polyester long afterglow composite material, which improves the luminous efficiency of polyester and realizes the adjustment of afterglow color.
[0006] In order to overcome the problem of single color afterglow, a color adjustment method (fluorescence resonance energy transfer method) based on this long afterglow composite material is provided, by adjusting the molar ratio of fluorescent dye and luminophore to adjust the energy transferred in the energy transfer process, so as to achieve multi-color, color-adjustable long afterglow and its application. And in order to overcome the limitations of high pressure, long preparation cycle, and complex process in the preparation of long afterglow composite materials in the prior art, a method for preparing long afterglow composite materials by simple heating is provided.
[0007] The technical solution of the present invention is as follows:
[0008] A boric acid-polyester long afterglow composite material, wherein the long afterglow composite material is prepared by uniformly mixing polyester and boric acid in a mass ratio of 1:1 to 1:100 (preferably 1:5 to 1:10), heating the mixture and restoring the mixture to room temperature to obtain a boric acid-polyester composite solid material with a long afterglow property.
[0009] The boric acid includes boric acid and dehydrated boric acid formed by dehydrating boric acid.
[0010] The polyester is specifically a molecule shown in one of the following:
[0011]
[0012] The present invention also provides a method for preparing the long afterglow composite material, comprising the following steps:
[0013] The polyester and boric acid are uniformly mixed in a mass ratio of 1:1 to 1:100, heated at 150°C to 300°C for 0.1min to 100min, and cooled to room temperature to obtain the long afterglow composite material.
[0014] The preparation method of the present invention also includes a simple method for adjusting the afterglow color, that is, adding fluorescent dyes in different proportions during the preparation of the long afterglow composite material can obtain a long afterglow composite material with adjustable afterglow color.
[0015] In some preferred embodiments, the fluorescent dye is an energy acceptor molecule that satisfies the fluorescence resonance energy transfer conditions, including: a combination of one or more of solvent red 197, solvent green 5, fluorescent yellow 3G, solvent orange 63, solvent red 242, cationic red FF or rubrene, and the structural formula is as follows:
[0016] The structural formula of the fluorescent dye is shown below:
[0017]
[0018] In some preferred embodiments, the mass fraction of the fluorescent dye is 1 to 50 parts, the mass fraction of the polyester is 1000 parts, and the mass fraction of the boric acid is 1000 to 100000 parts. The preparation method is to mix the fluorescent dye, polyester and boric acid evenly according to the feed ratio, heat at 150 to 300° C. for 0.1 to 100 minutes, and then return to room temperature to obtain a long afterglow composite material with adjustable afterglow color.
[0019] The present invention also provides applications of the long afterglow composite material and the color-adjusted long afterglow composite material.
[0020] The application is to mix the long afterglow composite material with polymer powder to form a luminescent material that can be processed and molded. The polymer powder includes: a combination of one or more of low-density polyethylene, high-density polyethylene, medium-density polyethylene, linear low-density polyethylene, polymethyl methacrylate, polyethyl acetate, polypropylene, polyvinyl chloride or polystyrene.
[0021] The application method of the long afterglow composite material before and after color adjustment is as follows:
[0022] The long afterglow composite material before or after color adjustment is mixed with a polymer material in a mass ratio of 1:2 to 1:10 as a characteristic luminescent material in a processable material, and after uniform mixing, heated at 120 to 220° C. to melt, processed and formed, and cooled to obtain a luminescent material model;
[0023] Or the long afterglow composite material powder before or after coloring is mixed with paraffin and saturated fatty acid as the characteristic luminescent material in luminescent crayons. The specific application method is to heat the mixture of saturated fatty acid and paraffin and the long afterglow composite material before or after coloring at a mass ratio of 1:2 to 1:10 at 120 to 220°C until melting, and use it for luminescent crayons after cooling; the mass ratio of saturated fatty acid to paraffin is 1:1 to 1:80; the paraffin is a combination of one or more selected from semi-refined paraffin, fully refined paraffin, microcrystalline paraffin, liquid paraffin and polyethylene wax, all of which can be obtained commercially; the saturated fatty acid includes stearic acid or palmitic acid, with a content of 95 to 100%, which can be obtained commercially.
[0024] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention. (In the following specific embodiments, the various technical solutions can be combined with each other in principle to obtain new technical solutions, which should also be regarded as specifically disclosed in the present invention.)
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a long afterglow polyester without rare earth elements, which overcomes the problems of limited rare earth material resources and high toxicity in luminescent polyester.
[0027] 2. The present invention provides a boric acid-polyester long afterglow composite material and a preparation method thereof by a simple heating method. The preparation method of the present invention is simple to operate and is expected to achieve mass production. The obtained long afterglow composite material has excellent luminescence performance and low cost, and has good application prospects.
[0028] 3. This method only requires one simple step to achieve energy transfer, making it easier to adjust the afterglow color. The afterglow color can be adjusted by controlling the ratio of donor and acceptor molecules and the type of fluorescent dye to obtain afterglow emission from blue to red, blue to green, and blue to yellow. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are the emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 1 of the present invention.
[0030] Figure 2 These are the emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 2 of the present invention.
[0031] Figure 3 These are the emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 3 of the present invention.
[0032] Figure 4 This is a lifespan decay curve diagram of the long afterglow composite material prepared in Example 1 of the present invention.
[0033] Figure 5 This is a lifespan decay curve diagram of the long afterglow composite material prepared in Example 2 of the present invention.
[0034] Figure 6 This is a lifespan decay curve diagram of the long afterglow composite material prepared in Example 3 of the present invention.
[0035] Figure 7 a. Delay spectrum and b. corresponding CIE coordinate diagram of the long afterglow composite material prepared in Example 9 of the present invention.
[0036] Figure 8 a. Delay spectrum and b. corresponding CIE coordinate diagram of the long afterglow composite material prepared in Example 12 of the present invention.
[0037] Fig. 9 This is a rendering of a luminous model made from the long afterglow composite material prepared in Application Examples 1, 2, and 3.
[0038] Fig.10 This is a photo of the luminous crayon effect made from the long afterglow composite material prepared in Application Examples 4, 5, and 6. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It is necessary to point out here that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0040] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0041] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0042] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0043] [Example 1]
[0044] 1000g of boric acid and 100g of polyethylene terephthalate (PET) were mixed evenly and heated at 210°C for 30min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 432nm, a phosphorescence lifetime of 1.512s, and a phosphorescence quantum yield of up to 58.89%.
[0045] [Example 2]
[0046] 870g of boric acid and 174g of polybutylene terephthalate (PBT) were mixed evenly and heated at 150°C for 100min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 424nm, a phosphorescence lifetime of 0.939s, and a phosphorescence quantum yield of up to 34.5%.
[0047] [Example 3]
[0048] 100g of boric acid and 100g of polyethylene 2,5-furandicarboxylate (PEF) were mixed evenly and heated at 270°C for 23min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 486nm, a phosphorescence lifetime of 0.624s, and a phosphorescence quantum yield of up to 21.91%.
[0049] [Example 4]
[0050] 660g of boric acid and 22g of polyethylene naphthalate (PEN) were mixed evenly and heated at 180°C for 45min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 512nm, a phosphorescence lifetime of 0.657s, and a phosphorescence quantum yield of up to 7.98%.
[0051] [Example 5]
[0052] 750g of boric acid and 15g of butylene adipate-co-butylene terephthalate (PBAT) were mixed evenly and heated at 260°C for 33min, and then restored to room temperature to obtain the long afterglow composite material. Its emission wavelength is 425nm, the phosphorescence lifetime is 1.123s, and the phosphorescence quantum yield can reach 23.16%.
[0053] [Example 6]
[0054] 500g of boric acid and 5g of polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG) were mixed evenly and heated at 300°C for 15 minutes, and then restored to room temperature to obtain the long afterglow composite material, which has an emission wavelength of 432nm, a phosphorescence lifetime of 1.072s, and a phosphorescence quantum yield of up to 33.25%.
[0055] [Example 7]
[0056] 760g of boric acid and 10g of polytrimethylene terephthalate (PTT) were mixed evenly and heated at 297°C for 40min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 433nm, a phosphorescence lifetime of 0.987s, and a phosphorescence quantum yield of up to 35.80%.
[0057] [Example 8]
[0058] 660g of boric acid and 20g of poly(trimethylene terephthalate) (PCT) were mixed evenly and heated at 200°C for 50min, and then restored to room temperature to obtain the long afterglow composite material, which had an emission wavelength of 435nm, a phosphorescence lifetime of 1.024s, and a phosphorescence quantum yield of up to 40.25%.
[0059] [Example 9]
[0060] 100g of boric acid, 10g of polyethylene terephthalate (PET) and 0.06g of solvent red 197 were mixed evenly and heated at 220°C for 50min, and then restored to room temperature to obtain the toned long afterglow composite material. The phosphorescence emission has a coordinate CIEx of 0.251 and a CIEy of 0.127 in the CIE diagram, and a phosphorescence lifetime of 0.835s.
[0061] [Example 10]
[0062] 55g of boric acid, 11g of polybutylene terephthalate (PBT) and 0.55g of solvent red 242 were mixed evenly and heated at 300°C for 0.1min, and then restored to room temperature to obtain the toned long afterglow composite material. The phosphorescence emission coordinates CIEx of the CIE diagram were 0.464, CIEy of the CIE diagram was 0.293, and the phosphorescence lifetime was 0.349s.
[0063] [Example 11]
[0064] 80g of boric acid, 80g of butylene adipate-co-butylene terephthalate (PBAT) and 0.28g of solvent orange 63 were mixed evenly and heated at 250°C for 25min, and then returned to room temperature to obtain the toned long afterglow composite material. The phosphorescence emission has a coordinate CIEx of 0.170 and a CIEy of 0.172 in the CIE diagram, and a phosphorescence lifetime of 0.728s.
[0065] [Example 12]
[0066] 2000g of boric acid, 20g of polyethylene terephthalate (PET) and 0.24g of solvent green 5 were mixed evenly and heated at 280°C for 100min, and then restored to room temperature to obtain the toned long afterglow composite material. The phosphorescence emission coordinates CIEx of the CIE diagram were 0.238, CIEy was 0.344, and the phosphorescence lifetime was 0.851s.
[0067] [Example 13]
[0068] 120g of boric acid, 12g of polyethylene terephthalate (PET) and 0.012g of fluorescent yellow 3G were mixed evenly and heated at 150°C for 30 minutes, and then restored to room temperature to obtain the color-adjusted long afterglow composite material. The phosphorescence emission coordinates CIEx of the CIE diagram are 0.186, CIEy is 0.239, and the phosphorescence lifetime is 1.102s.
[0069] [Example 14]
[0070] 1320g of boric acid, 22g of polyethylene terephthalate (PET) and 0.38g of cationic red FF were mixed evenly and heated at 180°C for 90min, and then returned to room temperature to obtain the toned long afterglow composite material. The phosphorescence emission has a coordinate CIEx of 0.398 and a CIEy of 0.243 in the CIE diagram, and a phosphorescence lifetime of 0.796s.
[0071] The emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 1 above are as follows: Figure 1 As shown, the emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 2 above are as follows Figure 2 As shown, the emission spectrum and delayed emission spectrum of the long afterglow composite material prepared in Example 3 above are as follows Figure 3 As shown; the life decay curve comparison diagram of the long afterglow composite material prepared in Example 1 is as shown Figure 4 As shown in the figure, the life decay curve comparison of the long afterglow composite material prepared in Example 2 is as follows Figure 5 As shown; the life decay curve comparison diagram of the long afterglow composite material prepared in Example 3 is as shown Figure 6 The delayed spectrum of the long afterglow composite material prepared in Example 9 and the CIE diagram of the afterglow color are shown as follows: Figure 7 The delayed spectrum of the long afterglow composite material prepared in Example 12 and the CIE diagram of the afterglow color are shown as follows: Figure 8 shown.
[0072]
Application Example 1
[0073] 55 parts by mass of the phosphor powder prepared in Example 9 and 165 parts by mass of low-density polyethylene were melt-blended at 180° C., and the luminescent model obtained after cooling emitted purple afterglow.
[0074]
Application Example 2
[0075] 30 parts by mass of the phosphor powder prepared in Example 12 and 60 parts by mass of high-density polyethylene were melt-blended at 220° C., and the luminescent model obtained after cooling emitted a green afterglow.
[0076]
Application Example 3
[0077] 315 parts by mass of the phosphor powder prepared in Example 13 and 1260 parts by mass of linear low-density polyethylene were melt-blended with the phosphor powder at 140° C. The luminescent model obtained after cooling emitted a cyan afterglow.
[0078]
Application example 4
[0079] 205 parts by mass of the phosphor powder prepared in Example 10, 205 parts by mass of palmitic acid and 205 parts by mass of fully refined paraffin were melt-blended at 60° C. and cooled to obtain a crayon emitting red afterglow.
[0080]
Application Example 5
[0081] 510 parts by mass of the phosphor powder prepared in Example 11, 121.4 parts by mass of palmitic acid and 2428.6 parts by mass of liquid paraffin were melt-blended at 130° C. and cooled to obtain a crayon emitting a light blue afterglow.
[0082]
Application Example 6
[0083] 505 parts by mass of the phosphor powder prepared in Example 14, 62.4 parts by mass of stearic acid and 4988.1 parts by mass of liquid paraffin were melt-blended at 150° C. and cooled to obtain a crayon emitting a pink afterglow.
[0084] The luminous model effects obtained in the above application examples 1-3 are as follows Fig. 9 As shown, the luminous crayons prepared in the above application examples 4-6 have the following effects: Fig.10 shown.
Claims
1. A boric acid-polyester long afterglow composite material, characterized in that: The long afterglow composite material is a boric acid-polyester composite solid material with long afterglow characteristics, which is formed by compounding boric acid and polyester material, wherein the mass ratio of polyester to boric acid is 1:1 to 1:
100.
2. The long afterglow composite material according to claim 1, characterized in that: The boric acid includes boric acid and dehydrated boric acid formed by dehydrating boric acid.
3. The long afterglow composite material according to claim 1, characterized in that: The polyester is a molecule shown in one of the following structures:
4. A method for preparing the long afterglow composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The polyester and boric acid are uniformly mixed in a mass ratio of 1:1 to 1:100, heated at 150 to 300° C. for 0.1 to 100 minutes, and cooled to room temperature to obtain a long afterglow composite material.
5. The preparation method according to claim 4, characterized in that: The steps also include adding fluorescent dyes in different proportions during the preparation of the long afterglow composite material to obtain a long afterglow composite material with adjustable afterglow color; The fluorescent dye is an energy acceptor molecule that meets the conditions of fluorescence resonance energy transfer: it includes one or more combinations of solvent red 197, solvent green 5, fluorescent yellow 3G, solvent yellow 33, solvent orange 63, solvent red 242, cationic red FF or rubrene, and the structural formula is as follows:
6. The preparation method according to claim 5, characterized in that: The method is: 1 to 50 parts by weight of fluorescent dye are weighed, uniformly mixed with 1,000 parts by weight of polyester and 1,000 to 100,000 parts by weight of boric acid, heated at 150 to 300° C. for 0.1 to 100 minutes, and then restored to room temperature to obtain a long afterglow composite material with adjustable afterglow color.
7. Use of the long afterglow composite material according to any one of claims 1 to 3 and the toned long afterglow composite material prepared by the method according to claim 5 or 6, characterized in that: The application is to uniformly mix the long afterglow composite material with polymer powder to prepare a luminescent material that can be processed and molded.
8. The use according to claim 7, characterized in that: The application method comprises the following steps: The long afterglow composite material powder and the polymer material powder are weighed in a mass ratio of 1:2 to 1:10, uniformly mixed, heated at 120 to 220° C. to be melted, processed and formed, and cooled to obtain a luminescent material model.
9. The use according to claim 7 or 8, characterized in that: The polymer powder includes: a combination of one or more of low-density polyethylene, high-density polyethylene, medium-density polyethylene, linear low-density polyethylene, polymethyl methacrylate, polyethyl acetate, polypropylene, polyvinyl chloride or polystyrene.
10. An application of the long afterglow composite material according to any one of claims 1 to 3 and the long afterglow composite material prepared by the method according to claim 5 or 6, characterized in that: Provided are luminous crayons and a formula thereof. The raw materials thereof include a mixture of saturated fatty acids and paraffin wax and the above-mentioned long afterglow composite material in a mass ratio of 1:2 to 1:10, which are heated to melt at 120 to 220° C. and used for luminous crayons after cooling; the mass ratio of the saturated fatty acid to the paraffin wax is 1:1 to 1:80; the paraffin wax is a combination of one or more selected from semi-refined paraffin wax, fully refined paraffin wax, microcrystalline paraffin wax, liquid paraffin and polyethylene wax, all of which can be obtained commercially; the saturated fatty acid includes stearic acid or palmitic acid, which can be obtained commercially.
Citation Information
Patent Citations
Preparation method of luminescent polyester fiber, its fabric and applications
CN111455652B
Preparation method of spectrum blue shift noctilucent fiber
CN112941660A
Organic room-temperature phosphorescent thin film materials with stimulus-responsive properties, their preparation methods and applications
CN113637195B
Organic room-temperature phosphorescent materials with multiple stimulus responses, their preparation methods, and applications
CN113735795B
Luminescent polyester master batch as well as preparation method and application thereof
CN115322529A